Fibrin-targeted direct factor Xa inhibition: construction and characterization of a recombinant factor Xa inhibitor composed of an anti-fibrin single-chain antibody and tick anticoagulant peptide - Hagemeyer, Christoph E.; Tomic, Ivo; Jaminet, Patrick; Weirich, Uta; Bassler, Nicole; Schwarz, Meike; Runge, Marschall S.; Bode, Christoph; Peter, Karlheinz (Thrombosis and Haemostasis, 2004)
We investigated whether the direct fXa inhibitor tick anticoagulant peptide (TAP) can be N-terminally coupled to a clot-targeting, single-chain antibody specific for fibrin (scFv59D8). Due to its unique position at the convergence point of the intrinsic and extrinsic pathways early in the coagulation cascade, factor Xa (fXa) represents an attractive therapeutic target. In contrast to indirect inhibitors, direct fXa inhibitors effectively inhibit clotbound and prothrombinase-associated fXa. Targeting of direct fXa inhibitors to clots promises to enhance local anticoagulative potency and to reduce systemic anticoagulation which potentially results in less bleeding complications. TAP is a highly potent fXa inhibitor. Since its N-terminus is essential for antifXa activity, it was a challenging question, whether TAP will be active as a N-terminally coupled fusion molecule. Two step affinity chromatography with Ni2+ and β15-22-peptide of human fibrin results in a pure 36 kDa protein, which was tested for its targeting function and anti-fXa activity. The recombinant fusion did not destroy the function of the fusion partners. Antibody binding function was on a par with the parent molecule. TAP activity was partially reduced, arguing that a free N-terminus is not required for anti-fXa activity, but is important for maximal potency. In human whole blood clots, scFv59D8-TAP revealed anticoagulative properties at concentrations (200 to 500 nM) where non-targeted TAP did not reveal anticoagulative activity at all. In summary, scFv59D8-TAP constitutes a promising new anticoagulant with fibrin-targeted factor Xa inhibition. The production in E. coli and the established purification methods are a solid basis for a modern, large scale production at low cost and reproducible activity.
Keywords: Coagulation inhibitors; drug design; fibrinogen / fibrin